EFFECT OF DRAINAGE GALLERY DIMENSIONS ON THE UPLIFT FORCE OF A GRAVITY DAM - M. A. El-Razek; M. M. A. Elela (International Association of Lowland Technology, 2002)
Uplift pressure on the floor of the gravity dam affects the stability of the dam. Therefore minimazing the uplift pressure force can be achieved by constructing a drainage gallery. In the present work, three parameters of the drainage gallery are studied experimentally on a sand model of gravity dam to determine their effect on the total uplift force acting on the floor of the dam. These parameters are the diameter of the drainage gallery (d), spacing of the drainage gallery in the longitudinal direction of the dam (L), and the penetration depth (h). It is found that, the penetration depth of the drainage gallery is more effective in reducing the uplift force than the other two parameters. The average values of reduction in the uplift force attributed to the change of d, L, and h accounted to about 11%, 25%, and 40% respectively.